Architectural design - Bielefeld, Bert (Basics (Basel, Switzerland), 2013)
This compilation of the volumes 'Design Ideas', 'Design Methods','Materials' and 'Spatial Design' in the successful student series Basics now gathers the fundamental topics of architectural design together in one book and thus in one context answers crucial questions concerning the hows and whys of the design processn--Source other than Library of Congress.